Influence of Genetic Polymorphisms on Response to Biologics in Moderate-to-Severe Psoriasis - Membrive Jiménez, Cristina (J Pers Med, 2021)
Psoriasis is a chronic inflammatory skin pathology of autoimmune origin and unknown etiology. There are various therapies for treating it, including a wide range of biopharmaceuticals indicated in moderate-to-severe psoriasis. Depending on their therapeutic target, they are classified as tumor necrosis factor inhibitors (anti-TNF) or cytokine inhibitors (interleukin-12, 23, and 17 antagonists). Although they have proved effective and safe, in clinical practice, many patients show a short- and long-term suboptimal response and even varying degrees of toxicity. This variability in response may be influenced by genetic factors, such as polymorphisms in the genes involved in the pathological environment, metabolism or mechanism of action of the drug that could affect the effectiveness and toxicity of biological therapies. This review assesses pharmacogenetic studies of the impact of genetic factors on response to biopharmaceuticals and toxicity in patients diagnosed with moderate-to-severe psoriasis. The results suggest that polymorphisms detected in the HLA genes, in genes that encode cytokines (TNF, IL genes, TNFAIP3), transporters (PDE3A-SLCO1C1, SLC12A8), receptors (TNFRSF1B, CD84, FCGR2A and FCGR3A, IL17RA, IL23R, TLR genes, PGLYRP4) and associated proteins (TNFAIP3, LY96, TIRAP, FBXL19), as well as other genes implicated in the pathogenesis of psoriasis (CDKAL1, CARD14, PTTG1, MAP3K1, ZNF816A, GBP6, CTNNA2, HTR2A, CTLA4, TAP1) can be used in the future as predictive markers of treatment response and/or toxicity with biological therapies in patients diagnosed with moderate-to-severe psoriasis, tailoring treatment to the individual patient.